A pilot, open-label, 8-week study evaluating desvenlafaxine for treatment of major depression in methadone-maintained individuals with opioid use disorder. (September 2018) - El Hage, Cynthia; Ghabrash, Maykel F.; Dubreucq, Simon; Brissette, Suzanne; Lespérance, François; Lespérance, Paul; Ouellet-Plamondon, Clairélaine; Bruneau, Julie; Jutras-Aswad, Didier
Abstract : Depression is one of the most prevalent psychiatric disorders among opioid-dependent individuals. Clinical trials testing selective serotonin reuptake inhibitors among depressed patients on methadone maintenance therapy (MMT) failed to show efficacy, whereas those on tricyclic antidepressants produced mixed results with potential for cardiotoxicity. Desvenlafaxine (DESV) is a SNRI with minimal cardiotoxicity and drug interactions. This study sought to assess feasibility and tolerability of using DESV in depressed patients on MMT. A total of 18 depressed individuals on MMT received DESV (50–100 mg/day) for 8 weeks. Participants were assessed for the following: (a) Safety of DESV using Systematic Assessment for Treatment Emergent Events-GI, ECG [corrected Q-T (QTc) interval measurement] and methadone serum levels; (b) depressive symptoms using Montgomery–Äsberg Depression Rating Scale (MADRS); and (c) other outcomes including anxiety, suicidality, craving, substance use, quality of life, and other depression scales. Registration number on ClinicalTrials.gov is NCT02200406. Among participants who completed the study, MADRS scores significantly decreased at week 8 compared with baseline. Responders and remitters on MADRS at week 8 were 61 and 50%, respectively. There was no significant change in [corrected Q-T (QTc) interval measurement] between baseline and week 4. DESV was well tolerated and associated with improvement of depressive symptoms. DESV may be a promising contender to treat depression in individuals on MMT and deserves further exploration in a randomized double-blinded clinical trial.